Strategi Pemerintahan Nagari dalam Pelaksanaan Pemerataan Bantuan Langsung Tunai di Nagari Kasang Kecamatan Batang Anai Kabupaten Padang Pariaman - Binti Tasakka, Nursyapika; Khaidir, Afriva (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research aims to understand how the implementation of the Nagari Government's strategy in distributing direct cash assistance is carried out and what factors hinder the equal distribution of direct cash assistance in Nagari Kasang, Batang Anai Subdistrict, Padang Pariaman Regency. The method used in this research is qualitative approach descriptive research. Data collection is obtained through interviews, observations, and documentation.The results of this research indicate that the Nagari Government's strategy in implementing the Equal Distribution of Direct Cash Assistance (BLT) in Nagari Kasang, Batang Anai Subdistrict, Padang Pariaman Regency, uses a system that encourages direct and inclusive participation of the community. Factors affecting the equal distribution of Direct Cash Assistance (BLT) in Nagari Kasang include delays in budget funds from the Padang Pariaman Government, causing uncertainty and affecting the distribution of Direct Cash Assistance (BLT). The distribution of Direct Cash Assistance (BLT) is carried out non-transparently and unfairly, leading to dissatisfaction among the community in the equal distribution process of this assistance, resulting in conflicts within the community. Based on the research results, it is hoped that the Nagari Kasang government will pay more attention to the equal distribution of Direct Cash Assistance (BLT) to prevent conflicts in the community.